Digital Leadership in Islamic Schools: The Mediating Role of Teacher Professionalism in Enhancing Student Digital Literacy through ICT Resource Management - Ariyani, Rika; Nasril, Nasril; Al Munip; Zh, Miftah Hur Rahman; Maspan; Darni; At Thaariq, Zahid Zufar (Edudeena : Journal of Islamic Religious Education, 2026)
Global digital transformation compels Islamic schools to harmonize religious values with modern competencies, necessitating effective digital Leadership and the management of ICT resources. This study aims to test an integrative model analyzing the direct and indirect effects of technology-driven Leadership and ICT resource management on teacher professionalism and student digital literacy within Islamic educational settings. A quantitative cross-sectional survey method was employed, involving 377 teachers from Islamic secondary schools in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that digital leadership exerts a powerful direct influence on both ICT resource management (β ≈ 0.99) and teacher professionalism (β ≈ 0.99). Teacher professionalism emerged as a key mediator and a stronger predictor of students’ digital literacy than mere ICT resource availability. The study concludes that the efficacy of digital leadership is enhanced by integrating Islamic values and recommends strengthening value-based leadership capacity and sustaining teacher professional development to achieve holistic educational excellence.